Implementation of Extreme Programming and Simple Additive Weighting for Web-Based Sales and Product Preference Analysis in Traditional Herbal Businesses - Sumardiono, Sumardiono; Priyadi, Wiwit; Wicaksono, Harjunadi; Santosa, Hadi; Sambath, Khoem; Liefalza, Andi Daffa (Compiler, 2025)
The rapid development of information technology encourages UMKM to adopt digital solutions to improve business effectiveness. This study aims to design a web-based herbal medicine sales information system at UMKM Griya Jamoe Klasik using the Extreme Programming (XP) method and implementing the Simple Additive Weighting (SAW) algorithm to analyze the best-selling herbal medicine products. The research approach used is quantitative descriptive, with data collection methods through observation, interviews, and questionnaires to 10 respondents over a period of one week. The criteria used in the analysis include price, taste, efficacy, and texture, each given a certain weight. The results of the SAW algorithm application show that the "Wedang Kencur" product is the best-selling herbal medicine with a preference value of 0.92, followed by "Wedang Mpon-mpon" at 0.85 and "Kunyit Asam" at 0.79. The system built is able to automate transaction recording, facilitate sales monitoring, and support accurate and fast data-based decision-making. This research contributes to increasing the competitiveness of UMKM in the digital era. Recommendations for further research are to expand the number of respondents, integrate online payment features, and develop mobile-based applications to reach a wider market.